2022
DOI: 10.1002/dc.25085
|View full text |Cite
|
Sign up to set email alerts
|

A unique case of anaplastic thyroid carcinoma comprising of two distinct patterns osteoclastic variant and squamous cell carcinoma in separate lobe imitating collision tumor: A case report

Abstract: Anaplastic thyroid carcinoma with two distinct morphologies in two lobes with no intermixing is very rare and not reported earlier. Furthermore, osteoclastic variant of anaplastic thyroid carcinoma as well as primary squamous cell carcinoma without any differentiated components are also very rare with only few reported cases describing their cytological features. Herein, we are reporting a unique and first case of anaplastic thyroid carcinoma comprising of two distinct patterns osteoclastic variant and squamou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…[7][8][9]19 Simply in view of the frequent BRAF V600E mutation, PAX8 expression, and sometimes TTF1expression, primary SCC of the thyroid has been considered as a type of ATC in the new classification system. 20 Xu et al 18 found primary SCC of the thyroid displayed BRAF V600E mutations in 60% of cases and had an outcome similar to ATC in general. In addition, these SCC expressed PAX8 and TTF-1 in 91% and 38% of cases, respectively, confirming their follicular cell origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9]19 Simply in view of the frequent BRAF V600E mutation, PAX8 expression, and sometimes TTF1expression, primary SCC of the thyroid has been considered as a type of ATC in the new classification system. 20 Xu et al 18 found primary SCC of the thyroid displayed BRAF V600E mutations in 60% of cases and had an outcome similar to ATC in general. In addition, these SCC expressed PAX8 and TTF-1 in 91% and 38% of cases, respectively, confirming their follicular cell origin.…”
Section: Discussionmentioning
confidence: 99%
“…However, the fifth edition of the WHO updates primary SCC of the thyroid as a histologic pattern of ATC rather than a separate entity 7–9,19 . Simply in view of the frequent BRAF V600E mutation, PAX8 expression, and sometimes TTF1expression, primary SCC of the thyroid has been considered as a type of ATC in the new classification system 20 . Xu et al 18 found primary SCC of the thyroid displayed BRAF V600E mutations in 60% of cases and had an outcome similar to ATC in general.…”
Section: Discussionmentioning
confidence: 99%